Practicalities of sustaining a goat-crossbreeding programme in eastern Ethiopia - Ayalew, W.; King, J.M.; Bruns, E.W.; Rischkowsky, Barbara A. (2002)
Crossbreeding of goats in traditional subsistence flocks had been promoted in selected villages of eastern Ethiopian highlands as a means to quick genetic progress based on the thesis that crossbreeding can increase the net contribution of goats. Observations on flock dynamics patterns of smallholder flocks with crossbred goats showed that the desirable attributes of crossbreeding had not been maintained after the promotion phase because: 1) the pool of crossbred goats was too small to maintain 50% exotic blood level in the crossbreeds; 2) shortages of crossbred breeding males also led to gradual back crossing of the does, resulting in an increasingly mosaic mix of crossbreeds; 3) the small size of flocks as well as their rapid turnover limited the scope for any selective breeding and the maintenance of superior breeding animals; and 4) losses control on the breeding of various classes of crosses with indigenous goats posed undesirable dissemination of introduced genes into the indigenous genetic pool. Therefore it was concluded that crossbreeding of indigenous goats with exotic breeds, as a technology for genetic improvement of smallholder goat flocks of Ethiopian highlands, is not sustainable under, subsistence mode of production.